Geotechnical synthesis of 2D-Electrical resistivity tomography of geomaterial – laboratory model study / Zainab Mohamed and Nurbaiyah Mohamad Noh - Mohamed, Zainab; Mohamad Noh, Nurbaiyah (Research Management Institute (RMI), 2011)
In this paper, a laboratory scale model study was conducted on interbeded geomaterial using electrical resistivity instrument. The electrical resistivity value of individual material was determined and modeled as mass scale. The tank was filled with composite geomaterial constituted of interbedding of cement mortar as hard layer and residual sedimentary soil. Forty-one copper electrodes of 15 cm long were used and installed at 4 cm spacing in the tank. The composite geomaterials were labeled as Model 1, Model 2 and Model 3, where they were referred respectively to interbedding of hard layer and layers of residual soil at natural dry state and wet state. The electrical resistivity terrameter was used to obtain the georesistivity pseudo-section by adopting Werner protocol. The georesistivity pseudo-sections were derived from 3 models simulated the subsurface of rock mass in humid tropic environment.The objective was to synthesize the composite georesistivity pseudo-section based on geo-engineering principle. It was observed that the pseudo-section of the composite geomaterial was represented by range of colors with range of georesistivity values. The horizontal bands of color differentiated the georesistivity of models vertically but constant in horizontal direction. The georesistivity value at material scale was comparable to the range of georesistivity values derived from the 2D electrical resistivity pseudo-sections. The contrasts in the conductivity of clay fraction, silica and electrolytes have differentiated the electrical resistivity pseudo-section of sandy soil mass and cement mortar hard material.